2002
DOI: 10.1016/s0735-1097(02)01804-1
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular dysfunction and risk of heart failure and mortality after myocardial infarction

Abstract: Right ventricular function is an independent predictor of death and the development of HF in patients with LV dysfunction after MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
303
1
11

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 400 publications
(333 citation statements)
references
References 28 publications
13
303
1
11
Order By: Relevance
“…Substudy from the SAVE study in subjects after MI with impaired LV function showed that RV dysfunction was an independent risk factor of total mortality, cardiovascular mortality and occurrence of CHF. Each 5% reduction in the RVFAC resulted in 16% increased odds of cardiovascular mortality [9]. Other studies showed, that in patients with advanced CHF and LV ejection fraction (LVEF) < 40% prognosis strongly depends on RV function.…”
Section: Right Ventricular Function In Chronic Heart Failurementioning
confidence: 99%
“…Substudy from the SAVE study in subjects after MI with impaired LV function showed that RV dysfunction was an independent risk factor of total mortality, cardiovascular mortality and occurrence of CHF. Each 5% reduction in the RVFAC resulted in 16% increased odds of cardiovascular mortality [9]. Other studies showed, that in patients with advanced CHF and LV ejection fraction (LVEF) < 40% prognosis strongly depends on RV function.…”
Section: Right Ventricular Function In Chronic Heart Failurementioning
confidence: 99%
“…Recent studies have reported that RV function has prognostic implications in several cardiovascular diseases (50)(51)(52). Of all cases of TCC, 13% involve RV (51).…”
Section: Right Ventricular Functionmentioning
confidence: 99%
“…In a state of right ventricular pressure overload this ventricular interdependence may be ascribed to pathologic septal motion, decreased LV preload or other unknown factors (Dittrich et al, 1989;Mizushige et al, 1989;Yu et al, 1996). RV function is an independent predictor of mortality and the development of heart failure (HF) in patients with known LV dysfunction (Zornoff et al, 2002) and right ventricular involvement during acute inferior myocardial infarction is a strong, independent predictor of major complications and in-hospital mortality (Zehender et al, 1993). Finally, 5-10% of patients with advanced chronic obstructive pulmonary disease (COPD) may suffer from severe pulmonary hypertension and present with a progressively downhill clinical course because of right heart failure added to the ventilatory handicap (Naeije, 2005).…”
Section: Introductionmentioning
confidence: 99%